Oral histories and the impact of archaeological fieldwork in contact encounters: meeting Socrates on the Omo. (30th August 2017) - Clack, Timothy; Brittain, Marcus; Turton, David
Abstract: Whilst there is growing concern within archaeology about the wider impact of archaeological research in general, only limited attention has so far been paid to the impact fieldwork has on local communities. Here, using examples from fieldwork with an agro‐pastoral Mursi community in Ethiopia's Lower Omo Valley, we present a case in which local oral traditions are modified in response to archaeological discoveries. This illustrates a particular example of the impact of fieldwork during and after its completion; and the enduring traces of contact upon fieldwork participants. We argue that in employing an attitude of impact practice within fieldwork that foregrounds the Socratic notion of dialogue, the resulting focus highlights the value and significance of archaeology to local communities.